Public-private partnerships in the road sector - Atmanand (2003)
Public-private partnerships (PPPs) represent a unique and flexible solution to road projects. PPPs can embrace a range of structures and concepts, which involve the sharing of risks and responsibilities between public and private sectors. Private sector involvement in the road sector in India has been under three routes, BOT route (build-operate-transfer), the annuity method and the SPV method (special purpose vehicle). In order to facilitate private sector participation in road projects in India, there should be a system of availability of long-term funds. Central road fund through cess on petrol and diesel is a new source of funds having significant importance. However, in case of successful PPP toll roads, it is imperative that the government should bear the responsibility of financing a part of total costs. - Reproduced.
Keywords: Roads